Delineating the climate change impacts on urban environment along with heat stress in the Indian tropical city - Halder B.; Chatterjee P.; Rana B.; Bandyopadhyay J.; Pande C.B.; Ahmed K.O.; Elkhrachy I.; Radwan N. (Elsevier Ltd, 2025)
India experiences significant levels of temperature variance as a result of urbanization, deforestation, and industrial growth, all of which contribute to a progressive increase in heat island effects. Significant landform change has occurred in Bhubaneswar City, Odisha, in recent decades as a result of major plant loss and temperature unpredictability. Thus, during the summer and winter months, an examination of the long-term heat island impacts is essential for Bhubaneswar. The evolution of landforms and heat island impacts in Bhubaneswar are evaluated using Landsat images from 1991 to 2021 datasets and correlation analysis of heat islands and geospatial variables. Between 1991 and 2021 with a 10-year gap, the landforms studied showed an increase in built-up land (38.009 km2), a decrease in vegetation (13.875 km2), bare ground (16.306 km2), and water bodies (7.828 km2). The annual temperature variance in Bhubaneswar was 0.124 C (summer), and 0.293 C (winter). Surface temperatures varied by about 3.71 C (summer) and 8.80 C (winter). During the study years, heat islands increased from 2.89 to 4.27 (summer) and 2.30 to 3.87 (winter). In Bhubaneswar, there was an increase in ecological variation of 0.092 (summer), and 0.071 (winter). There is a statistically significant negative correlation between the R2 values and the temperature and the built-up indices. Using this dataset, administrative and development authorities can choose which measures to take to counteract the effects of variations in thermal variation. Finding out how man-made land use structures, industrial zones, and other areas contribute to the built-up area a direct consequence of heat islands was the aim of this study. ? 2024 Elsevier Ltd